Uses and results of social networks as an electoral strategy: case analysis of four municipalities of gran Concepcion (Chile) in the 2016 campaign - Zurita Arriagada, Lesly (2016)
The process of disaffection in the political activity in Chile and the legal amendments to the electoral propaganda and the financing of campaigns in the country generated that parties and candidates could see social networks as an opportunity of dissemination and adverti- sing through the Internet. However, the practice shows that, despite its manifest importance, the activity has not reached an edge of professionalization yet. This explanatory research depicts the use of digital platforms specifically in four Chilean cities during the 2016 munici- pal election. Based on that information, there will be a critical reflection on the role of the journalist and social communicator in the design of relevant communication strategies in the electoral activity.